Milk fermented with the probiotic candidate Lactobacillus paracasei FT700 induces differentiation of monocytes toward macrophages in vitro. (May 2015) - Tulini, Fabrício Luiz; Hymery, Nolwenn; Choiset, Yvan; Chobert, Jean-Marc; Haertlé, Thomas; De Martinis, Elaine Cristina Pereira; Le Blay, Gwenaelle
Highlights: FT700 tolerated simulated gastric conditions. The strain hydrolyzed milk proteins during milk fermentation. Fermented milk stimulated in vitro differentiation of monocytes in macrophages. FT700 has potential to be used as a probiotic in functional fermented milk products. Abstract: Lactobacillus paracasei FT700 was tested for its survival in simulated gastrointestinal conditions ( in vitro ) and for its sensitivity to antibiotics. The strain was used to produce fermented milk and the cell-free supernatant was freeze-dried and applied in cell cultures (monocytes and macrophages) to evaluate its cytotoxicity and immunomodulatory effects. After 180 min at pH 2.0 or in simulated gastric juice, L. paracasei FT700 concentrations were reduced by 4 and 3 log cfu/mL, respectively. Moreover, the strain was susceptible to the majority of antibiotics tested. Freeze dried cell-free fermented milk supernatant (FMS) was toxic to monocytes after 72 h of exposure at 10 mg/mL inducing their apoptosis. However, at concentrations below toxic level, FMS stimulated the differentiation of monocytes into macrophages, as observed by the increased expression of CD71 marker. This immune stimulation was not inflammatory since low production of TNF-α was observed. Overall, L. paracasei FT700 has potential to be used as probiotic in functional fermented milk.